2019
DOI: 10.1200/cci.18.00147
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization Risk During Chemotherapy for Advanced Cancer: Development and Validation of Risk Stratification Models Using Real-World Data

Abstract: PURPOSE Hospitalizations are a common occurrence during chemotherapy for advanced cancer. Validated risk stratification tools could facilitate proactive approaches for reducing hospitalizations by identifying at-risk patients. PATIENTS AND METHODS We assembled two retrospective cohorts of patients receiving chemotherapy for advanced nonhematologic cancer; cohorts were drawn from three integrated health plans of the Cancer Research Network. We used these cohorts to develop and validate logistic regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 37 publications
0
44
2
Order By: Relevance
“…Brooks et al 4 developed a logistic regression model to predict hospitalizations in a cohort of 1579 patients receiving palliative chemotherapy at a single institution, with a C statistic of 0.71 based on internal bootstrapping. In a subsequent study, Brooks et al 14 used logistic regression to predict hospitalizations among 4240 patients with stage IV or recurrent solid tumors within 3 Kaiser Permanente regional health systems. Their model included 2 variables, albumin and sodium, and had a C statistic of 0.69 in the validation cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brooks et al 4 developed a logistic regression model to predict hospitalizations in a cohort of 1579 patients receiving palliative chemotherapy at a single institution, with a C statistic of 0.71 based on internal bootstrapping. In a subsequent study, Brooks et al 14 used logistic regression to predict hospitalizations among 4240 patients with stage IV or recurrent solid tumors within 3 Kaiser Permanente regional health systems. Their model included 2 variables, albumin and sodium, and had a C statistic of 0.69 in the validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although several existing risk scores predict specific toxic effects from chemotherapy such as febrile neutropenia, 10,11,12 prediction scores for acute care use have focused only on hospitalizations after starting palliative chemotherapy for solid tumors and have not used population-based data. 13,14 To our knowledge, to date, population-based studies on acute care use during systemic treatment for cancer have focused mostly on a single cancer type or considered few risk factors and have not generated a predictive model. 15,16,17,18,19…”
Section: Introductionmentioning
confidence: 99%
“… 9 In most countries, cancer treatments for diagnosed patients have been postponed, especially immunosuppressive therapies and invasive procedures, such as surgery, which require hospitalisation and admission to intensive care units in some cases. 10 WHO has reported that cancer services have been partially or completely disrupted in a third of countries in Europe. 11 For example, the Netherlands experienced a 25% decrease in cancer diagnoses during the first COVID-19 wave in February to April, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy may also be appropriate in other settings, including for patients undergoing systemic therapy, which has been the subject of many prediction models. 9,10,27,28 We additionally evaluated reasons for visits to determine if certain types of acute care were preventable. CMS-designated preventable diagnoses during RT were less common reasons for acute care in the intervention arm, though more data may be required to understand which acute care visits are truly preventable.…”
Section: Discussionmentioning
confidence: 99%
“…We previously developed a ML algorithm utilizing patient electronic health record (EHR) data, which retrospectively demonstrated strong predictive ability to identify patients at high risk for acute care, 8 comparing favorably to other models for this complex problem. 9,10 Despite a growing body of retrospective medical ML literature, 11,12 prospective evaluation remains tremendously limited, primarily to diagnostic fields. [13][14][15][16] Despite the need for prospective interventional trials, 17 there have been few, including a recent trial effectively predicting intraoperative hypotension utilizing arterial catheter sensor data.…”
Section: Introductionmentioning
confidence: 99%